PROFESSORAS QUE ENSINAM MATEMÁTICA E UM DENOMINADOR COMUM: GRUPO COLABORATIVO (Revista Contexto & Educação, 2020)
We analyze the movement of the constitution of a collaborative work group, specifically, the role of the process of reflection on the practice, opportunized by the reflective recording of two members from the photography and video recording of the Geometry classes. The theoretical reference covers questions related to the teacher's learning that teaches Mathematics in the environment of the collaborative groups, as well as the process of their ongoing formation based on reflective practice. The methodology adopted falls within the field of qualitative, descriptive-analytical studies, in which experience reveals characteristics of collaboration in the collective discussion space as a promising aspect of data production procedures. The final results allow us to infer that teachers had their practices modified from the direction of the activities proposed in the group based on the dynamics of registering and sharing classes, a central issue that raised the need to write, narrate and / or record their own performance as a source of professional development. This fact has also brought to the understanding that in the sharing of actions, the subject recognizes himself as the protagonist of his activity and can contribute to the doing of the other, corroborating the assertion "what is lacking in me is left in you."
Keywords: Mathematics Education. Collaborative Group. Reflection on Practice.